COVID-19 patient satisfaction and associated factors in telemedicine and hybrid system - Dagmawit G. Gashaw; Zewdie Aderaw Alemu; Freddy Constanzo; Freddy Constanzo; Feben T. Belay; Yakob W. Tadesse; Carla Muñoz; Juan Pablo Rojas; Cristobal Alvarado-Livacic (Frontiers Media S.A., 2024)
BackgroundThe quality assessment of the home-based isolation and care program (HBIC) relies heavily on patient satisfaction and length of stay. COVID-19 patients who were isolated and received HBIC were monitored through telephone consultations (TC), in-person TC visits, and a self-reporting application. By evaluating patient satisfaction and length of stay in HBIC, healthcare providers could gauge the effectiveness and efficiency of the HBIC program.MethodsA cross-sectional study design enrolled 444 HBIC patients who answered a structured questionnaire. A binary logistic regression model assessed the association between independent variables and patient satisfaction. The length of stay in HBIC was analyzed using Cox regression analysis. The data collection started on April (1-30), 2022, in Addis Ababa, Ethiopia.ResultsThe median age was 34, and 247 (55.6%) were females. A greater proportion (313, 70.5%) of the participants had high satisfaction. Higher frequency of calls (>3 calls) (AOR = 2.827, 95% CI = 1.798, 4.443, p = 0.000) and those who were symptomatic (AOR = 2.001, 95% CI = 1.289, 3.106, p = 0.002) were found to be significant factors for high user satisfaction. Higher frequency of calls (>3 calls) (AHR = 0.537, 95% CI = 0.415, 0.696, p = 0.000) and more in-person visits (>1 visit) (AHR = 0.495, 95% CI = 0.322, 0.762, p = 0.001) had greater chances to reduce the length of stay in the COVID-19 HBIC.Conclusion70.5% of the participants had high satisfaction with the system, and frequent phone call follow-ups on patients' clinical status can significantly improve their satisfaction and length of recovery. An in-person visit is also an invaluable factor in a patient's recovery.